DONOR SITE MORBIDITY IN DORSALIS PEDIS FLAP - J. L. SRIVASTAVA; S. P. BAJAJ; V. K. TIWARI; R. P. NARAIN (Indian Journal of Plastic Surgery)
The present paper is based on a study of Eleven cases where Dorsalis pedis flap has been used. Donor site morbidity was observed in eight of them which required subsequent hospitalisation and medical care. The factors responsible for this have been highlighted.